The effect of job satisfaction and organizational culture on employee performance in autofinance business: the mediating role of organizational commitment - Azmy, Ahmad; Wiadi, Iyus (Zielona Góra: Faculty of Economics and Management Press)
The present study analyzed the mediating role of organizational commitment in the effect of job satisfaction and organizational culture on employee performance. Job satisfaction and organizational culture may influence mployee performance. The variable with the most significant effect on employee performance was analyzed hrough job satisfaction and organizational culture.
Keywords: job satisfaction; organizational culture; organizational commitment; employee performance